PENERAPAN MODEL VERHULST PADA JUMLAH PRODUKSI KELAPA SAWIT DI KOTA LANGSA - Rihadatul Aishy; Nabilla, Ulya; Nurviana (JURNAL GAMMA-PI, 2025)
Palm oil is one of the main commodities that plays a crucial role in supporting the regional economy, including in Langsa City. However, annual palm oil production has shown fluctuations, necessitating a mathematical model to understand and predict its growth pattern. This study aims to estimate the amount of palm oil production in Langsa City and to evaluate the accuracy of the estimation results using the Mean Absolute Percentage Error (MAPE) method. The data used consist of annual palm oil production from 2018 to 2024, obtained from the Central Bureau of Statistics (BPS) of Langsa City.The research stages include determining the carrying capacity (K) and growth rate (r), constructing the Verhulst logistic model, and calculating MAPE to assess model accuracy. The analysis results show that the estimated palm oil production in 2025 is 736 tons. The obtained MAPE value of 40.48% indicates that the model’s accuracy is still relatively low in predicting palm oil production. This may be due to the fluctuating nature of production data and the limited observation period. Nevertheless, the Verhulst logistic model remains a relevant initial approach to understanding the dynamics of palm oil production growth in Langsa City.